Size-dependent behaviours of functionally graded sandwich thin-walled beams based on the modified couple stress theory - Bui, Xuan-Bach; Nguyen, Trung-Kien; Karamanli, Armagan; Vo, Thuc P. (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2023)
This paper examines the static and vibration analysis of functionally graded sandwich thin-walled microbeams using the modified couple stress theory. The material properties in both web and flanges vary continuously through their thickness. The equations of motion are derived and solved by the Ritz method. Verification studies are performed on the bending and vibration responses of FG sandwich thin-walled beams. The effects of material distribution, span-to-height's ratio, and material length scale parameters on the responses of microbeams for various boundary conditions are investigated. The results of the analysis indicate that the deflections and natural frequencies of functionally graded sandwich thin-walled microbeams are greatly influenced by the variations of parameters mentioned earlier. The microbeams with the size effect are predicted to be much stiffer than their macro counterparts. Some benchmark results can be used as a reference for future studies.
Keywords: Static; Vibration; Functionally graded sandwich thin-walled mi; crobeams; Size effects; Modified coupled stress theory; DYNAMIC STIFFNESS MATRIX; FREE-VIBRATION; BUCKLING BEHAVIORS; I-BEAMS; MICROBEAMS; COMPOSITE; PLASTICITY; STABILITY; Engineering